Autopercepción de la imagen corporal en los estudiantes del Instituto Superior Tecnológico Beatriz Cueva de Ayora Loja. - Azuero Encalada, Johanna Thalía (2017)
Adolescence is a period of very rapid changes in the life of the adolescent in which his body as a child is transformed into adult body, with inevitable psychological and psychosocial repercussions; Especially students have a self-perception of their body image, which can be good or bad, in the latter case causes alterations in food and self-esteem, negatively impacting the emotional state of the adolescent. The present study is carried out at the "Beatriz Cueva de Ayora" Higher Technological Institute, which is located at Orillas del Zamora Avenue and 10 de Agosto in the city of Loja in zone 7 of Ecuador. This is a descriptive study that aimed to identify self-perception of body image in students of the "Beatriz Cueva de Ayora" Higher Technological Institute of Loja, the BSQ Cooper questionnaire modified in 2013 was used as instrument. The results show that 44% of the students manage a low and very low level of self-perception, insofar as the high level of self-perception in relation to sex does not have a significant difference; The students with low level of self-perception of the corporal image are those of Tenth year corresponding to the age of 14 years. In conclusion, the students of the Higher Technological Institute "Beatriz Cueva de Ayora" Loja, present low levels of self-perception of the body image since these are generally produced by a dissatisfaction of their body image. KEYWORDS Self-esteem, Self-perception of Body Image, Body Image Dissatisfaction, adolescent.